ANALISIS TEKNIK DAN FINANSIAL UNIT PENANGKAPAN MUROAMI DI PERAIRAN KEPULAUAN SERIBU - Mochammad Prihatna Sobari; Isnaini Isnaini (Buletin PSP, 2009)
The objective of this research was determined of influence from activity of the yellow tail resources utilization with the profit and feasibility level of the yellow tail fisheries effort in territorial Seribu Islands waters.  The research was did by descriptive method, the sample was did by purpo-sive sampling.  Data analysis used the technique and financial analysis.  The result indicate that the actual condition of the yellow tail resources utilization give profit level of the muroami unit is Rp 384,751,272 per year and R/C is 1.09.  Pursuant to investment criterion, NPV value of muroami unit is Rp 8.980.639,29, Net B/C 1,06 and IRR is 18%, so that the muroami unit competent be achieved and developed, but very sensitive to price change of fuel (diesel fuel and carosene) equal to 2,5%.Key words: financial analysis, Seribu Islands, technique analysis